Assessment of organochlorine pesticide residues in edible oil (Annals of Bangladesh Agriculture, 2025)
Organochlorine pesticides (OCP) are persistent in nature, highly toxic, and bio-accumulative. Their presence in different food items is a serious health concern for human being. Therefore, a total of ten edible oils were collected from the local market of Gazipur and Bogura districts of Bangladesh to assess the contamination of OCP residues. Modified AOAC version 2009.01 method was used to extract and clean up the sample. Detection and quantification of residue was done by gas chromatograph equipped with electron capture detection system. On an average 26.87% of the oil samples were found contaminated with at least one OCP residues. A total of sixteen organochlorine pesticides were detected such as α-BHC, ß-BHC, γ-BHC, δ-BHC, heptachlor, heptachlor epoxide, α-chlordane, γ-chlordane, α-endosulfan, aldrin, dieldrin, endrin, p,p´-DDD, p,p´-DDE, o,p´-DDT, and p,p´-DDT. Residues of α-chlordane, ß-BHC, heptachlor and heptachlor epoxide were detected in ≥ 40% of the total samples of edible oils. However, the residue levels were either very small (less than 0.02 ppm) or not detected at all in sesame, sunflower, rice bran, coconut, groundnut and palm oils. The majority of the OCPs contamination observed in oils of mustard, soybean, rice bran, olive and black cumin. The levels of heptachlor in soybean oil (0.021 mg.kg-1) was found slightly higher than the recommended MRL (0.02 mg.kg-1). Whereas the heptachlor epoxide in olive oil (0.10 mg.kg-1) was found much higher than the recommended limit. Both alpha and gamma chlordane were found equal to the recommended limit (0.020 mg.kg-1) in soybean oil. DDTs residues were observed in mustard, soybean, rice bran and black cumin oils but their individual occurrence was found below the MRL. But their cumulative DDTs (i.e ΣDDT = p,p´-DDD + p,p´-DDE + o,p´-DDT + p,p´-DDT) was found higher than the recommended limit in soybean oil (0.085 mg.kg-1) only. Coconut, groundnut and palm oil did not have any OCP residues. The tolerable daily intake (TDI) was measured for impact assessment of ΣBHC, Σheptachlor, Σchlordane, ΣDDTs and ΣOCPs and found that the daily intake level of these OCPs by the people was found below the TDI. Therefore, the tested edible oils are safe for human consumption. However, the study suggested for periodical monitoring to ensure safe consumption of edible oils.Ann. Bangladesh Agric. 28(1): 127-143